Nationalism in Internationalism - Holmes, Michael. author. aut Link
XVII, 138 p. 4 illus.
Keywords: This book interprets the relationship between Ireland and the European Union (EU). We are coming up to 50 years since Ireland acceded to the EU (2023), and the links between the two are unique and distinctive. This volume presents an original interpretation of Irish-EU relations, and this in turn has implications for a wider understanding of the EU. Its aim is to analyse the Irish-EU relationship from the idea of two apparently contradictory political ideas – internationalism (as represented by European integration in this particular instance) and nationalism (long the dominant value in Irish politics). The authors argue that to date the contradictions have been managed with considerable ease, leading us to characterise the Irish-EU relationship as “nationalism within internationalism.” Michael Holmes is Associate Professor of Political Science at ESPOL (European School of Political and Social Sciences) at the Catholic University of Lille, France. His research focuses mainly on Ireland and the EU and on the impact of European integration on political parties. Kathryn Simpson is Associate Professor of Economics and Politics of the European Union at Keele Business School and School of Social, Political and Studies at Keele University, UK. Her research focuses on public opinion, political behaviour and attitudes towards the EU, in particular in Ireland and the UK in the context of Brexit.